Survival and reproduction tests using springtails reveal weathered petroleum hydrocarbon soil toxicity in boreal ecozone - Roy, Prama; Rutter, Allison; Gainer, Amy; Haack, Elizabeth; Zeeb, Barbara (Environmental science and pollution research international, 2024)
Survival and reproduction tests were conducted using two native springtail (subclass: Collembola) species to determine the toxicity of a fine-grained (< 0.005 – 0.425 mm) soil from an industrial site located in the Canadian boreal ecozone. Accidental petroleum hydrocarbon (PHC) release continuously occurred at this site until 1998, resulting in a total hydrocarbon concentration of 12,800 mg/kg (soil dry weight). Subfractions of the PHC-contaminated soil were characterized using Canadian Council of Ministers of the Environment Fractions, which are based on effective carbon numbers (nC). Fraction 2 (> nC 10 to nC 16 ) was measured at 8400 mg/kg and Fraction 3 (> nC 16 to nC 34 ) at 4250 mg/kg in the contaminated soil. Age-synchronized colonies of Folsomia candida and Proisotoma minuta were subject to 0%, 25%, 50%, 75%, and 100% relative contamination mixtures of the PHC-contaminated and background site soil (< 100 mg/kg total PHCs) for 28 and 21 days, respectively. Survival and reproduction decreased significantly (Kruskal–Wallis Tests: p < 0.05, df = 4.0) in treatments of the contaminated site soil compared to the background soil. In both species, the most significant decline in survival and reproduction occurred between the 0% and 25% contaminated soil. Toxicity responses in the two springtails were ascribed to the standardized test design, short lifespans, and high fecundity in both species. This study showed that 25 + years of soil weathering has not eliminated the toxicity of fine-grained PHC-contaminated soil on two native terrestrial springtail species. Adverse effects to springtail health were attributed to exposure to soils dominated by genotoxic PHC Fraction 2 compounds and slow weathering processes due to the cold climate at the site.